Pengaruh Disiplin Kerja dan Kreativitas Karyawan terhadap Kinerja Karyawan (Studi Kasus Hotel Permata Lampung Barat) - Patmarina, Hepiana; Mubarak, Ahmad Rais Rozan (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2026)
The problem underlying this research is the continued presence of customer complaints regarding service delays and the lack of initiative from employees in meeting customer needs, which indicates the need to improve aspects of work behavior. This study aims to determine the effect of work discipline and employee creativity on employee performance at the Permata Hotel, West Lampung. This study uses a quantitative method. A survey was conducted by distributing questionnaires to 87 hotel customers as respondents with a purposive sampling technique. Data were analyzed using validity and reliability tests, multiple linear regression, t-test, f-test, and coefficient of determination with the help of SPSS 25 software. The findings explain that partially, both work discipline and employee creativity have a positive and significant effect on employee performance. Simultaneously, both variables also have a significant effect. This finding focuses on improving the quality and capability of human resources in the hospitality sector to create superior and satisfying services.